1996
DOI: 10.1093/oxfordjournals.eurheartj.a014905
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term effects of exercise training on the tonic autonomic modulation of heart rate variability after myocardial infarction

Abstract: We studied the effects of cardiac rehabilitation on the sympathovagal control of heart rate variability in 30 patients after a first, uncomplicated myocardial infarction. Twenty-two patients completed 8 weeks of endurance training (trained), while eight decided not to engage in the rehabilitation programme for logistical reasons, and were taken as untrained controls. Age, site of infarction, ejection fraction, ventricular diameter and stress test duration were similar in the two groups at baseline. Heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 24 publications
3
61
0
6
Order By: Relevance
“…Our results are confirmed by that of Jurca et al in 2004 who, after 8 weeks of moderate exercise training in females, showed improved vagal modulation of heart rate on 10-min resting ECGs [36]. Many previous studies done on diseased populations to evaluate the effect of short-term exercise intervention on short-term HRV modification assessed only supine variables [37][38][39][40][41][42][43]. Sandercock et al in 2007 observed significant increases in the supine RR interval, SDRR, LF(ln) and HF In the present study, only the RR interval increased significantly in the supine position, while the other variables did not show significant changes in favour of the exercise group.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are confirmed by that of Jurca et al in 2004 who, after 8 weeks of moderate exercise training in females, showed improved vagal modulation of heart rate on 10-min resting ECGs [36]. Many previous studies done on diseased populations to evaluate the effect of short-term exercise intervention on short-term HRV modification assessed only supine variables [37][38][39][40][41][42][43]. Sandercock et al in 2007 observed significant increases in the supine RR interval, SDRR, LF(ln) and HF In the present study, only the RR interval increased significantly in the supine position, while the other variables did not show significant changes in favour of the exercise group.…”
Section: Discussionsupporting
confidence: 88%
“…Similar studies, e.g. on diabetic [43,45] and cardiac patients [38,40,41], had equal or even less participants. Heart rate variability was the only tool used to assess the function of the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 86%
“…(57) found that following an eight-week cardiac rehabilitation program, 21 male and 17 female participants had significant increases in HRV parameters compared with those not participating in the training program. In another study (58), researchers reported a 25% increase in SDNN, a 69% increase in the square root of the mean of the sum of squares of successive N-N interval differences, a 120% increase in the number of successive N-N intervals differing by more than 50 ms divided by the total number of successive N-N intervals and a 30% reduction in LF/HF ratio after 22 MI patients completed an eight-week endurance rehabilitation program. These improvements continued to be observed at one year following participation in the eight-week training program.…”
Section: Exercise Therapy and Hrv Modification In Clinical Populationsmentioning
confidence: 96%
“…Specifically, the incidence of sudden cardiac death is inversely related to the level of regular physical activity (3). Regular physical activity also reduces the incidence of cardiac arrhythmias in individuals with cardiac disorders (7,38,49,55,70,71,79). For example, regular physical activity improved cardiac function and reduced the arrhythmia frequency in individuals with congestive heart failure (27,40).…”
mentioning
confidence: 99%